Effect of detergent, herbs and spices on the growth of Vibrio parahaemolyticus biofilm in seafood - Nillian, Elexson (2014)
The aim of this study was to investigate the effects of detergent, herbs, and spices on antimicrobial activity and specificity to mitigate the growth of V. parahaemolyticus biofilm. A total of 394 samples were collected from wet markets (n=201) and hypermarkets (n=193), consisting of cockles (Anadara granosa), clams (Mya arenaria), shrimps (Penaeous spp.) and squids (Loligo opalescens). The prevalence of 9.14% (36/394) of positive toxR genes, 63.8% of positive isolates contained virulent genes of V. parahaemolyticus tdh+, 22.2% of V. parahaemolyticus trh+, and 5.56% (2/36) of positive isolates in both V. parahaemolyticus tdh+ and trh+ had been detected. The thirty six (n=36) isolates were further tested with antibiotic susceptibility test and they werefound to be resistant to at least seven out of eighteen antibiotics. V. parahaemolyticus isolates (97.2%) showed Multiple Antibiotics Resistance index > 0.2, indicating that these isolates might have originated from high risk source. Next, RAPD-PCR was carried out to investigate the relationship between genetic diversity and clonal among the strains. As dendogram was generated among the four groups, group Type B was the largest group that possessed 92.86% (13/14) of isolates from bivalve seafood, such as cockles and clams. The samples were derived from wet markets and they are closely related. RAPD-PCR fingerprinting and antibiotic resistance profiling indicated multiple antibiotics resistant V. parahaemolyticus were wide-spread among the groups. The isolates were examined in the assessment of biofilm producer at different temperatures. V. parahaemolyticus could form biofilm and presence of biofilm was detected at 37 ºC (optimum temperature), followed by room temperature (25 ºC), and 4°C (chiller temperature). The representatives of clonal from each group, which wereresistant antibiotics ofV. parahaemolyticus, were examined for effect of detergents. Out of the three detergents; Detergent 1 (Linear Alkylbenzene sulphonate based), Detergent 2 (Quaternary Ammonium based), and Detergent 3 (Sodium Hydroxide based) with minimum concentration of 100 mg/ml (100,000 µg / ml), Detergent 1 was found to be the most effective. As for Detergent 1, the Minimum Inhibition Concentrations (MICs) ranged from 97.656 - 1562.5 µg/ml, while the Minimal Bactericidal Concentrations (MBCs) were at 781.25 - 3125 µg/ml. Meanwhile, inhibition time assay showed that the bactericidal activity of detergent was fast-acting against antibiotics resistant V. parahaemolyticus at 8× MIC within 1 hr and the reduction in CFU/ml was 3 log units (99.9%) with P value < 0.05 was considered statistically significant. The growth of antibiotics resistant V. parahaemolyticus biofilm was inhibited at 1562.5 – 6250 µg/ml and was eradicated at 3125 – 12500 mg/ml. Then, the study was furthered by using natural antimicrobial herbs and spices in inhibiting and in preventing the growth of V. parahaemolyticus biofilm. Out of the twenty herbs and spices, four of them, whichwere cloves, star anise, lemon leaves, and curry leaves, showedsome activities towards the antibiotics resistant isolates. At a minimum of 10 mg/ml (1000 µg/ml), clove was the most effective as it showed MICs at 19.531-78.125 µg/ml and MBC at 78.125-625 µg/ml. The killing time activity with cloves was fast-acting against antibiotic resistant V. parahaemolyticus at 8× MIC in 0.5hr time, while 1 hr, 4 hr, and 8 hr with star anise, lemon leaves, and curry leaves extracts. The reduction in CFU/ml was 3 log units (99.9%). Besides, cloves demonstrated concentration that ranged from 78.125 – 156.25 µg/ml, and 312.5 – 625 µg/ml to inhibit and to totally eradicate the growth of antibiotic resistant V. parahaemolyticus biofilm. Thus, these findings can be used to mitigate the resistance of biofilm growth in any food supply chain related to seafood in future.